SAT0026 Pro-Resolving and Cartilage-Protective Actions of Resolvin D1 in Inflammatory Arthritis. (15th July 2016) - Norling, L.; Headland, S.; Dalli, J.; Arnardottir, H.; Jones, H.; Haworth, O.; Serhan, C.; Perretti, M.
Abstract : Background: Dietary supplementation with fish oils has proved efficacious in reducing joint pain, swollen joint count and NSAID usage in RA patients, yet there is an unmet need to determine how they act. Omega-3 PUFA, which are abundant in fish oils are precursors to a new genus of protective bioactive lipids comprised of lipoxins, resolvins, protectins and maresins (collectively termed specialised pro-resolving mediators (SPM)). Objectives: We hypothesised that SPM may offer a molecular mechanism for the beneficial effects of omega-3 consumption in RA patients. We tested the anti-arthritic potential of a specific SPM; Resolvin D1 (RvD1), in an inflammatory polyarthritis model and investigated novel mechanisms of action. Methods: Metabololipidomic profiling on murine arthritic joints or human synovial fluids was performed by LC-MS/MS. Murine arthritis was induced by transfer of K/BxN serum. Mice were treated with 100ng AT-RvD1 daily either prophylactically or therapeutically ensuing overt signs of arthritis. Histology and flow cytometry was performed to assess joint leukocyte infiltrate. Human chondrocyte micromasses were cultured to assess chondroprotective actions of RvD1. Results: Arthritic joints obtained from mice supplemented with an omega-3 rich diet contained elevated levels of protective SPM, and human RA synovial fluid analyses with LC-MS/MS revealed physiologically active levels of RvD1. Mice treated with a stable epimer of RvD1 (17 R -RvD1) exhibited significantly attenuated arthritis severity, cachexia, hind-paw oedema and paw leukocyte infiltration and shortened the remission interval. Mechanistically, metabololipidomic profiling in arthritic joints revealed AT-RvD1 significantly reduced LTB4, TXB2 and prostaglandin biosynthesis, whilst selectively enhancing levels of protective SPM. AT-RvD1 stimulated genes associated with cartilage matrix synthesis, exhibited chondroprotection in vitro and direct intra-articular treatment prevented arthritis induced cartilage degradation. Joint protective actions of AT-RvD1 were abolished in ALX (fpr2/3) null mice, indicating the essential role of this receptor in mediating AT-RvD1 actions. Conclusions: These studies indicate that this SPM offers a valuable therapeutic approach for inflammatory joint diseases including RA. Acknowledgement: This work was funded by the Arthritis Research UK (Career Development Fellowship 19909 to L.V.N.) and Wellcome Trust Programme grant 086867/Z/08/Z to M.P. This work forms part of the research themes contributing to the translational research portfolio of Barts and the London Cardiovascular Biomedical Research Unit, which is supported and funded by the National Institutes of Health Research. Disclosure of Interest: None declared